Study of thermal stability of two acid phosphatases from breadfruit (Artocarpus communis) seeds: kinetic and thermodynamic analysis (Journal of Basic and Applied Research in Biomedicine, 2022)
The thermal stability of acid phosphatases ACP1 and ACP2 from breadfruit (Artocarpus communis) seeds was investigated by studying the effect of heat treatment over a range of 55 to 75 °C. Thermal inactivation of each enzyme, evaluated by loss in activity, was apparently followed by first-order kinetics with k-values comprised between 0.0139 ± 0.0005–0.0620 ± 0.0001 and 0.0117 ± 0.0002–0.0362 ± 0.0004 min-1 for ACP1 and ACP2, respectively. D and k-values decreased and increased, respectively, with increasing temperature, indicating faster inactivation of ACP1 and ACP2 at higher temperatures. Ea and Z-values were estimated to 69.19 ± 2.71 kJ/mol and 31.55 ± 1.05 °C for ACP1, 52.25 ± 1.94 kJ/mol and 41.84 ± 2.06 °C for ACP2. Thermodynamic parameters were also calculated. All the results suggest that both acid phosphatases are relatively resistant to long heat treatments up to 60°C.